2018
DOI: 10.1007/s00192-018-3730-3
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review of intra- and post-operative complications with minimal versus large space of Retzius infiltration at the time of retropubic TVT placement

Abstract: This retrospective review revealed the potentially beneficial effect of the large (180 ml × 2) bilateral SORI with retropubic TVT placement in terms of the reduction in risk of bladder perforation. It also showed no potential added risk of post-operative complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Some authors suggest various modifications of the TVT procedure to reduce the risk of cystotomy. Ras et al [25] reported a beneficial effect of a large (2 × 180 ml of saline with bupivacaine and adrenaline) bilateral space of Retzius infiltration. McLennan et al [26] proposed an abdominal needle placement (top-down) instead of the vaginal (bottom-up) approach.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest various modifications of the TVT procedure to reduce the risk of cystotomy. Ras et al [25] reported a beneficial effect of a large (2 × 180 ml of saline with bupivacaine and adrenaline) bilateral space of Retzius infiltration. McLennan et al [26] proposed an abdominal needle placement (top-down) instead of the vaginal (bottom-up) approach.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, which prospectively followed 149 patients undergoing R-MUS placement, retropubic hydrodissection did not significantly reduced bladder perforation rates 10 —a finding echoed in our study. In a more recent publication by Ras et al, 11 comparing bilateral retropubic injections of small (<70 mL per site) and large volume (180 mL per site), trocar-related bladder injury only occurred in the small volume group; however, this study was limited by sample size and lacked power to give procedure-related recommendations to avoid bladder injury. Although these injected volumes were much larger than those originally described by Ulmsten and Petros, 2 our data, which is based on a large cohort of patients, do not support the recommendation to inject before trocar placement to prevent trocar-related bladder injury.…”
Section: Discussionmentioning
confidence: 86%
“…9 Given conflicting evidence regarding predictive factors for bladder perforation during R-MUS placement, and lack of evidence to support adoption of techniques to minimize such injury, studies are needed to further elucidate factors predictive of bladder injury. 10,11 Thus, the primary objective of our study was to describe the incidence of and factors associated with bladder perforation at the time of R-MUS placement. Secondary objectives were to examine the effect of retropubic hydrodissection on rates of bladder perforation and to describe whether patients who experience a trocar-related bladder injury experience a higher incidence of other adverse events.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, iatrogenic bladder injury may result in increased postoperative pain, urinary retention, urinary tract infections, and retropubic hematoma. 4,5 Unrecognized bladder perforation can lead to postoperative dysuria, recurrent urinary tract infections, urinary frequency, urgency, pelvic pain, and bladder calculi on exposed sling material. Unrecognized iatrogenic bladder injury requires additional revision surgery with at least partial mesh sling removal and can result in a return of SUI.…”
Section: Openmentioning
confidence: 99%